The Relationship Between Physcial Activity and Psychological Well-Being: A Narrative Literature Review - Muhammad Oktapian Nur Rajab; Amung Ma'mun; Syarifatunnisa Syarifatunnisa (Physical Activity Journal (PAJU), 2025)
Students' psychological well-being plays an important role in supporting their cognitive, social and emotional development. Physical activity is known to have a positive impact on mental health through physiological and psychological mechanisms, such as the release of endorphins and increased self-confidence. This article uses a narrative literature review approach to explore the relationship between physical activity and students' psychological well-being, by summarizing the results of previous research. Results show that physical activity can reduce symptoms of stress, anxiety and depression, and improve overall quality of life. The article also discusses the challenges of implementing physical activity programs in school settings and provides recommendations for effective interventions.